Success of ceftazidime–avibactam and aztreonam in combination for a refractory biliary infection with recurrent bacteraemia due to blaIMP-4 carbapenemase-producing Enterobacter hormaechei subsp. oharae. Issue 8 (6th August 2021) - McKew, Genevieve; Merlino, John; Beukers, Alicia; van Hal, Sebastian; Gottlieb, Thomas
Abstract : Background. Infections due to metallo-beta-lactamase (MBL)-producing organisms are becoming a significant problem, and antibiotic treatment options are limited. Aztreonam inhibits MBLs, and its use in combination with ceftazidime–avibactam (CAZ–AVI–AZT) to inhibit other beta-lactamases shows promise. Methods. A 45-year-old woman suffered from recurrent and sustained MBL ( bla IMP-4)+ Enterobacter cloacae complex bacteraemia from an undrainable biliary source, and had failed nine alternative antibiotic regimens over a 5-month period. The 10th episode was successfully treated with CAZ–AVI–AZT, and she has had no further relapses. Three of the isolates underwent whole-genome sequencing (WGS) on the MiSeq platform and were analysed with the Nullarbor pipeline. Results. A layered Etest method for synergy between CAZ–AVI and aztreonam demonstrated an MIC of 2 mg l −1 for the combination. Isolates were identified by WGS as Enterobacter hormaechei subsp. oharae . All three of the isolates had bla TEM-4 ESBL, bla OXA-1 and bla ACT-25. Two of the carbapenem-resistant isolates contained bla IMP-4. Conclusion. While aztreonam inhibits MBLs, MBL-positive isolates often express other beta-lactamase enzymes. Avibactam inhibits ESBLs and other beta-lactamases, and its use in this case possibly contributed to therapeutic success due to inhibition of the concomitant bla TEM-4 in the isolates. This case demonstrates that phenotypic antimicrobial susceptibility testing (layered Etests for synergy), backed up by WGS, can produce results that allow tailored antimicrobial therapy in difficult infections. This case adds to the evidence for using CAZ–AVI–AZT in serious MBL infections.